Uniform ZnO epitaxial films formed at atmospheric pressure by high-speed rotation-type mist chemical vapor deposition. (18th November 2015) - Tanoue, Hironobu; Taniguchi, Takuya; Wada, Shohei; Yamamoto, Shinya; Nakamura, Shohei; Naka, Yoshihiro; Yoshikawa, Hiroyuki; Munekata, Mizue; Nagaoka, Shoji; Nakamura, Yusui
Abstract: Uniform ZnO epitaxial films were formed on 2-in.-diameter m -plane sapphire substrates by high-speed rotation-type mist chemical vapor deposition at atmospheric pressure, without using any vacuum equipment. The ZnO films were characterized by scanning electron microscopy, X-ray diffraction in θ–2θ and ϕ scanning modes, electron backscatter diffraction, and room-temperature photoluminescence measurements. Experimental results show that m -plane ZnO films were epitaxially grown on the m -plane sapphire substrates with high uniformity of not only thickness but also crystallinity and optical properties. These results will promote the progress of ZnO-based devices such as light-emitting diodes.